STEVIA THE SWEET PLANT. CAN IT GROW IN TABASCO? - Gayosso Rodríguez, Salomé; Estrada Botello, Maximiano Antonio (Kuxulkab’, 2021)
The stevia plant (’Stevia rebaudiana’ Bertoni) is used worldwide as a natural sweetener. Its cultivation is mainly due to its high content of glycosides and its medicinal properties. The main producer worldwide is China, but in recent years its cultivation has spread to other countries, especially in Latin America. In Mexico, it is a relatively new and innovative crop. Due to the generation of jobs and the health benefits, stevia could be a cultivation proposal for the state of Tabasco. However, its sensitivity to humidity and the lack of information related to its local adaptation make its cultivation questionable. For this reason, to know its adaptation, growth, and production under the environmental conditions of the area, Morita II variety stevia plants were established in the community of La Huasteca, Centro, Tabasco during the period from December 2019 to March 2020.